Peningkatan Kualitas Pegawai melalui Program Autocad : Pendekatan Social Exchange Theory - Riza Bahtiar Sulistyan Bahtiar (Universitas Lancang Kuning, 2021)
The existence of technology in the world of work is very necessary in the current era and will make a worker more quickly complete his work. The problem that occurs is the lack of knowledge to operate an autocad program that can accelerate the completion of work, especially related to development planning. Training is needed to improve employee knowledge and abilities. The method used in the form of stages of preparation, implementation, and evaluation as well as implementation. The results show that the training activities are in accordance with what is expected and in accordance with the application of social exchange theory, namely the perceived benefits of the organization for giving employees the opportunity to attend training. An assessment of the success of the training has shown results that are above predetermined standards. Although it is not yet optimal, training activities can provide benefits felt by the organization.